Pola Dermatom pada Herpes Zoster di Poliklinik Kulit dan Kelamin RSUP Dr. M. Djamil Padang - Putri Sabila Hidayat; Rina Gustia; Satya Wydya Yenni (Jurnal Ilmu Kesehatan Indonesia, 2020)
Abstract Background. Herpes zoster is a skin disease caused by reactivation of varicella zoster virus after its primary infection and characterized by the onset of a skin rash with a dermatomal distribution and accompanied by severe pain. The cases of herpes zoster have tended with increasing age. Objectives. This study was aimed to obtain the dermatome pattern of herpes zoster in the Dermatovenerology Polyclinic of Dr. M. Djamil Hospital Padang period 2015-2017. Method. This study was a descriptive study that was conducted in May 2018-August 2018. Simple size was 18 patients suited by inclusion criteria. Data were obtained from medical records of herpes zoster patients and presented in the frequency distribution tables. Results. The results showed that thoracic dermatome and trigeminal nerve area were most commonly involved (44.4%), within the age range of 45-64 years old (33.3%). There is no differences in events between men and women (50%). Pain is the most common major subjective complaint (88.2%) and classical grouped vesicles is the most major objective complaint (92.9%). Most patients have complications (72.2%), common complication is the neurological (38%). Conclusion. The location of dermatomes for herpes zoster patients in the the Dermatovenerology Polyclinic of Dr. M. Djamil Hospital Padang was a thoracic region of 8 patients (44.4%) and a trigeminal nerve area of ​​8 patients (44.4%). Keywords: : dermatome, herpes zoster